Land Cover Classification Using Sentinel 2A Image in Kolaka Subdistrict, Kolaka Regency, Southeast Sulawesi - Suni, Muhammad Adam; Fitra, Ramad Arya; Umar, Mohamad Fahrul Himalaya (PT. Riset Press International, 2023)
Land cover in Kolaka District continues to change. Mapping and identifying land cover types using the Maximum Likelihood method is more accurate than other methods. This research aims to analyze the capabilities of Sentinel 2A Imagery and the Maximum Likelihood classification method for mapping and identifying land cover types in Kolaka District. This research was carried out from July to September 2023 and was carried out in 4 stages, namely the first stage of image pre-processing by carrying out the layer stacking process. The second stage is image analysis and classification. The third stage is carrying out a Ground Check, and the fourth stage is validation and accuracy testing. The value of the accuracy test results with Overall Accuracy (OA) is 88.75% which is in the good category. The results of the land cover classification obtained 8 land cover classes, namely secondary dry land forest covering an area of 3974.20 Ha or 31.84%, plantation land cover covering an area of 3,886.87 Ha or 31.14%, dense bushes covering an area of 1,641.42 Ha or 13.15%, mixed dry land agricultural land cover covering an area of 1,415.62 Ha or 11.34%, residential land cover of 744.26 or 5.96%, paddy field cover of 613.53 Ha or 4.92%, open land cover of 148.66 Ha or 1.19% and water body land cover of 56.22 Ha or 0.45% of the total area of Kolaka District.